Molecular identification of Cryptosporidium spp. in animal and human hosts from the Czech Republic - Hajdusek, Ondrej; Ditrich, Oleg; Slapeta, Jan (Veterinary parasitology, 2004)
To study the diversity of Cryptosporidium spp. in various hosts, we used the variability of the small-subunit rRNA gene and the Cryptosporidium oocyst wall protein genes. Oocysts from humans, cattle, horses, dogs, field mice, chickens, reptiles, deer, goat, cat, antelope and from a sample of water reservoir were assayed. The zoonotic C. parvum bovine genotype sequence was found to be present in the most of isolates. This study shows a complex epidemiology pattern for C. parvum bovine genotype infections. The identification of cattle, horse, and deer isolates emphasizes a transmission route for C. parvum via these hosts, and identifies a potential source for human infection in the Czech Republic. Furthermore, C. andersoni from a cow, C. baileyi from a chicken, C. felis from a cat, C. meleagridis from a dog, and C. saurophilum and C. serpentis from reptiles were also identified in the isolates from the Czech Republic.
Keywords: polymerázová řetězová reakce; DNA, Protozoan; sekvence aminokyselin; Cattle; lidé; Base Sequence; RNA, Ribosomal; skot; Cryptosporidiosis; Infant; dítě; Humans; sekvenční seřazení; Polymerase Chain Reaction; Protozoan Proteins; protozoální DNA; fylogeneze; Česká republika; Zoonoses; předškolní dítě; Child, Preschool; kryptosporidióza; zvířata; Czech Republic; Animals; molekulární sekvence - údaje; Molecular Sequence Data; Sequence Alignment; Child; Phylogeny; zoonózy; Amino Acid Sequence; protozoální proteiny; sekvence nukleotidů; RNA ribozomální; kojenec; Cryptosporidium